2021
DOI: 10.1159/000519154
|View full text |Cite
|
Sign up to set email alerts
|

The Low Maternal Consumption of Homemade Fermented Foods in Pregnancy Is an Additional Risk Factor for Food Protein-Induced Allergic Proctocolitis: A Case-Control Study

Abstract: <b><i>Introduction:</i></b> Food protein-induced allergic proctocolitis (FPIAP) is the most common non-IgE-mediated food allergy and it varies between 4% and 8% in infants. The aim of the study was to evaluate the potential association between FPIAP in infants and maternal daily consumption of homemade fermented foods (FFs) during pregnancy. <b><i>Methods:</i></b> Two hundred and seven infants were included in this case-control study, 106 with physician-diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Of these, 1372 studies were deemed irrelevant and excluded (Figure 1), and 74 records were further reviewed using full texts. Finally, 32 studies with nearly 190,000 subjects were deemed eligible for inclusion in this meta‐analysis, 16–47 where one study compared two separate cohorts 47 (Table 1). Using the Newcastle–Ottawa Scale, 27 and 6 studies were considered as high and moderate quality, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 1372 studies were deemed irrelevant and excluded (Figure 1), and 74 records were further reviewed using full texts. Finally, 32 studies with nearly 190,000 subjects were deemed eligible for inclusion in this meta‐analysis, 16–47 where one study compared two separate cohorts 47 (Table 1). Using the Newcastle–Ottawa Scale, 27 and 6 studies were considered as high and moderate quality, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…There were 17 studies which evaluated the association between maternal active smoking during pregnancy and offspring eczema development, 16,17,20,[22][23][24][25][26][27][28][29]31,34,37,41,43,46 6 studies for food allergy 17,21,23,33,45,47 and 2 studies for food sensitisation. 17,18 There was no significant association between maternal active smoking during pregnancy and the risk of eczema development when all assessment types were considered (RR = 0.92; 95% CI 0.84-1.00; Figure 2).…”
Section: Maternal Active Smokingmentioning
confidence: 99%
See 1 more Smart Citation
“…Karatas and colleagues reported that a higher maternal educational level was associated with an increased risk of FPIAP [ 53 ]. There is documentation of an association between lower parenteral education and socioeconomic status, with a poorer quality of diet and an increased risk of asthma, along with low adherence to asthma medication use being observed [ 54 ].…”
Section: Discussionmentioning
confidence: 99%